Development of User Interface Based on LabVIEW for Unmanned Aircraft Application - Faaris Mujaahid; Amir Malik Hizbullah; Febrian Dhimas Syahfitra; Muhammad Abduh Dahlan; Nugroho Dwi Juliansyah (Universitas Muhammadiyah Yogyakarta, 2017)
This paper describes the user interface construction of rocket/aircraft condition monitoring systems on LabVIEW, a graphical-based programming language. The interface, placed in the ground station, has some important information transmitted from the rocket. The information contains real-time data from the sensor devices. The aim of the construction of this interface is that the operator in the ground station can monitor the behavior and the condition of the flying rocket, in regard to the self-control mechanism programmed within the rocket. The LabVIEW front panel includes the visualization of 3D rocket motion, accelerometer-graph, gyroscope-graph, rocket navigation, GPS positioning, altitude, and pressure-meter. The result proved that the data transmission was recorded properly to the front panel system and logbook. In addition to the result, the reliability test has 50% probability to the system performance with the given test period of 300 seconds and 600 seconds. The low reliability result might be caused by the size of buffer overflow between the hardware and LabVIEW.